The Development of Aboriginal Language Programs: A Journey towards Understanding - Graham, Barbara (Canadian Journal of Education/Revue canadienne de l'éducation, 2005)
Attempts to build intercultural understanding inevitably uncover tensions and involve negotiating issues of identity, power, and resistance. Using a self‐study approach, I describe the development and early implementation phase of Aboriginal language programs in one school district. I consider the collaborative process involving representatives from the school district, community, and Aboriginal agencies to suggest strategies to transform material and discourse conditions in the community through dialogue and norms of reciprocity. I show that adopting traditional narratives and incorporating cultural structures into school practices demonstrates an integrated approach to communicating and responding to community concerns leads to greater understanding across cultures. Key words: Aboriginal language programs, intercultural understanding;, community involvement, school change Les efforts en vue de promouvoir les relations interculturelles mettent inévitablement en relief des tensions et impliquent la prise en compte des questions d’identité, de pouvoir et de résistance. L’auteure décrit l’élaboration des programmes de langue destinés aux autochtones dans un arrondissement scolaire et la première phase de leur mise en œuvre. Le processus, fruit d’un effort concerté entre l’arrondissement scolaire, des membres de la communauté et des organismes autochtones, a non seulement dévoilé des zones de conflit et de tension entre les attentes communautaires et les politiques et pratiques des écoles, mais également fourni des occasions d’étudier ces zones. En apprenant à estomper les frontières entre l’école, la communauté et les cultures, les participants ont réussi à transformer les conditions matérielles et les discours à travers le dialogue et des normes de réciprocité. Mots clés : programmes de langue autochtones, promotion des relations interculturelles, participation communautaire, évolution de l’école.